Pemberian Sorgum Sebagai Substitusi Jagung Dalam Ransum Terhadap Persentase Karkas dan Non Karkas Ayam Broiler Umur 6 Minggu - Ronaldus Rochi; Ni Ketut Sri Rukmini; Luh Suariani (Fakultas Pertanian, Universitas Warmadewa, 2019)
The needs for animal protein consumption is increasing in line with the increasing population growth. Various attempts have been made to meet the needs including by raising broiler. In order that broiler achieve optimal productivity, a proper ration feeding both in quality and in quantity is crucial. One of such alternative feed supplies is sorghum, which is easily found throughout Indonesian regions and has nutritional substance comparable to corn at a relatively cheaper price. Therefore, this research was conducted to find out the effects of the provision of sorghum as maize substitution on the carcass and non-carcass percentage of six-week broiler, with provision level of up to 28%. This study uses 45 broilers of CP-707 strain. The method used is CRD (completely randomized design) with 5 treatments and 3 replications. The treatment included rations with no sorghum addition (R0), ration with 7% sorghum addition (R1), ration with 14% sorghum addition (R2), ration with 21% sorghum addition(R3) and ration with 28% sorghum addition (R4). The variables observed in this study were weight, carcass weight, carcass percentage, non-carcass weight and non-carcass percentage. Based on the results, it is concluded that the addition of sorghum into the poultry ration in all treatments has no effect on carcass weight, percentage of carcass, non-carcass weight, and percentage of non-carcass of the six-week broiler, but the addition of sorghum at the level of 28% reduced the weight and is significantly different statistical-wise (P <0.01). To save the cost of poultry feed in broiler farms, it is recommended that farmers use sorghum at the level of 21% as an alternative substitute of corn.